Ongoing Neotectonic Activity in the Timiskaming ─ Kipawa Area of Ontario and Québec - Doughty, Michael; Eyles, Nick; Daurio, Louise (Geoscience Canada, 2010)
SUMMARY The Timiskaming Graben lies along the border of Ontario and Québec within the Western Québec Seismic Zone – a conspicuous belt of heightened intracratonic seismic activity in eastern Canada. The graben forms a prominent 50-km wide fault-bounded morphotectonic depression partly filled by Lake Timiskaming (ca. 100 km long and 200 m maximum depth). This lake is a postglacial successor to the much larger glacial Lake Barlow, which drained about 8000 years ago, leaving an extensive clay plain (Little Clay plain). Some 1000 kilometres of high resolution seismic sub-bottom data collected from Lake Timiskaming reveal that both late-glacial Barlow and postglacial Holocene sediments are extensively deformed by neotectonic horst and graben structures. The bathymetry of the lake floor is structurally controlled by faulting; graben basins record enhanced postglacial subsidence between parallel bounding faults, one of which is expressed onshore on the surrounding clay plain as a 20-km long, 10-m high scarp. These structures indicate ongoing neotectonic activity on a scale not recognized elsewhere across intracratonic North America. Seismic reflection data confirm the Timiskaming Graben as an intraplate ‘weak zone’ that may contain a long, late Cenozoic sediment record. A program of deep continental drilling within the Timiskaming Graben and extension of the current program of investigating lake-floor geology across the many lakes of the Western Québec Seismic Zone are now needed.